O SKUTKOWOŚCI PRZESTĘPSTW FORMALNYCH - Nowak, Paweł (Zeszyty Prawnicze, 2016)
CRIMINAL CONSEQUENCES OF FORMAL OFFENCES Summary The author discusses the concept of criminal consequence in Polish law. Debate is still going on in the theory and jurisdiction of Polish criminal law on whether a particular crime or offence should be classified as formal (przestępstwa formalne) or as consequential (przestępstwa skutkowe – viz. crimes/offences incurring criminal consequences; cf. inchoate crimes or offences). A point which turns out to be particularly problematic in this respect is the definition of criminal consequence, to enable a distinction to be drawn between formal and consequential (inchoate) offences/crimes. The author concludes that in practice all offences and crimes have a consequence. If a state in which a specific danger has emerged may be treated as a criminal consequence, it should also be admissible to treat a state in which an abstract danger has been created as a criminal consequence. Viewed from this aspect, all crimes are formal; for instance incitement is committed the moment when its perpetrator addresses words encouraging the commission of a crime to another person.